Respon Petani Terhadap Kebijakan Pengendalian Alih Fungsi Lahan di Kecamatan Bojongsoang Kabupaten Bandung - Insani, Fitrah Rahmah; Setiawan, Iwan; Trimo, Lucyana (Universitas Galuh, 2025)
Land had significant aspect in agriculture production. Economically, land turns out to be an asset for the farmers and becoming an important factor for the economic growth. However, it appears that land conversion is getting out of control and apprehensively affecting negative for farmers and their environments. This research aims to analyze factors that influence farmers response towards land conversion. This research use quantitative methods using Structural Equation Modelling (SEM) with software LISREL 8.80. Data was obtained by simple random sampling interview towards respondents. The result shows that factor that has indirect significant effect towards farmers characteristics (t-value 8,17) and driving factors (t-value 8,33). Whereas factor that has direct significant effect towards the response is communication (t-value 9,02)